Pelatihan Perhitungan Harga Pokok Produksi Di Umkm Kripik Ketela desa Pulo Kiton, Bireuen - Ritonga, Zuriani; Kamaruddin; Zuhra, Fatimah; Zalikha; Jannah, Nur; Elvina; Ekobroto, Bayu; Lubis, Junita (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Determining the cost of production may still be somewhat difficult for MSME players. Calculation and determination of the cost of production is very important in order to know the calculation of sales margins, determination of selling prices and predictions of profit and loss. UMKM Keripik Ketela has not yet calculated the cost of goods produced accurately due to a lack of knowledge about accounting. Conducted training regarding calculating the cost of production according to It is hoped that accounting science can produce accurate information and can be used as a consideration in determining product selling prices more accurately. In calculating the cost of a product, it is necessary to know the cost elements used, including the nature of these costs, both fixed and variable. The training program provided will help Cassava Chip MSME owners to be able to accurately calculate the cost of production which will later be useful in determining product selling prices, monitoring periodic profits and losses.